Adjustable annular rings of periodic surface structures induced by spatially shaped femtosecond laser. (31st March 2015) - Wang, Cong; Luo, Zhi; Duan, Ji'an; Jiang, Lan; Sun, Xiaoyan; Hu, Youwang; Zhou, Jianying; Lu, Yongfeng
Abstract: In this study, we propose a favorable method to modulate femtosecond laser Gaussian beams into annular beams by using an axicon for the fabrication of periodic surface structures. Adjustable annular rings of uniform oriented periodic surface structures with a period of approximately 600 750 nm are fabricated in one illumination step without complicated movements of the translation stage. The orientations of the fabricated periodic surface structures are controllable by changing the electric vector of the laser beam. In addition, by adjusting the distance between the sample and microscope objective, the diameters of the fabricated annular rings can be flexibly controlled in a wide range without changing the optical elements and realignment of the optical path.